2018
DOI: 10.1159/000490310
|View full text |Cite
|
Sign up to set email alerts
|

Concern about Falling and Complexity of Free-Living Physical Activity Patterns in Well-Functioning Older Adults

Abstract: Background: Fall-related psychological concerns are common among older adults, potentially contributing to functional decline as well as to restriction of activities and social participation. To effectively prevent such negative consequences, it is important to understand how even very low concern about falling could affect physical activity behavior in everyday life. We hypothesized that concern about falling is associated with a reduction in diversity, dynamics, and performance of daily activities, and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(65 citation statements)
references
References 37 publications
1
64
0
Order By: Relevance
“…It is possible that the imbalance disruption imposed by unstable surfaces improved not only the balance but also increased the confidence of the UST group older adults to perform greater complexity tasks in their everyday life context. This hypothesis can be supported by Paraschiv‐Lonescu et al, who concluded that older adults capable of performing more complex tasks have less concern about falling. Future studies should confirm the preventive role of this exercise mode in both healthy and clinical populations at risk of falling (ie, multimorbidity and frailty individuals).…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that the imbalance disruption imposed by unstable surfaces improved not only the balance but also increased the confidence of the UST group older adults to perform greater complexity tasks in their everyday life context. This hypothesis can be supported by Paraschiv‐Lonescu et al, who concluded that older adults capable of performing more complex tasks have less concern about falling. Future studies should confirm the preventive role of this exercise mode in both healthy and clinical populations at risk of falling (ie, multimorbidity and frailty individuals).…”
Section: Discussionsupporting
confidence: 91%
“…Our approach of looking at PA pattern complexity of the barcodes, as previously proposed for other populations [ 28 , 29 ], is completely new in children with CP. We believe that this approach outreaches simple activity count, as it takes into consideration other aspects such as variety and temporal dynamics of barcode states.…”
Section: Discussionmentioning
confidence: 99%
“…In a future study, this approach could be transferred into real-life with the same population, and compared to our five-sensor set-up for validation. Methods to use single-sensor data for PA barcoding have been described and used in well-functioning older adults [ 29 ]. Providing these metrics with a single-sensor measurement could offer a simplified alternative to the comprehensive five-sensor set-up we used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations